R.E.D Touch Bridal Studio / Eruphrasia Michelle Ak Kennedy - Kennedy, Eruphrasia Michelle; Awg Ahmad, Dyg. Zuraida; Patang, Regina (2011)
Our company's name is RED Touch Bridal Studio. The nature of the business is providing products and services for bridal. Our business is an enterprise and it consists of three members. We all agreed to become a partner in this business and contribute a certain amount of capital for the business as stated in the agreement. The main business activity is to provide whether products or services such as wedding gown. We understand that, as a bride who is getting married, they want their wedding to be an event where it can be remembered for their entire life. We are not just giving them to feel the wedding is just an event but to give new dimension of wedding to them while giving our services to them, we also want to become as a part of their family in preparing their wedding day. This is because; we highlighted the sense of belongingness in preparing the customer's wedding where it meets our concept which is accurate.Next thing is. R.E.D Touch Bridal Studio is operating from 10 a.m-9 p.m. on weekdays and on weekend and holidays it operates from 10 aan-5p.m